ANALISIS PEMAHAMAN MASYARAKAT MENGENAI LAYANAN DAN PRODUK TERHADAP BANK SYARI???AH DALAM MINAT MENABUNG (STUDI KASUS DI DESA SERI TANJUNG) - Ratna; Ayuni Vinka (LA RIBA: Jurnal Perbankan Syariah, 2022)
The purpose of this study is to determine the analysis of public understanding of services and products for Islamic banks in the interest of saving in Seri Tanjung Village. The method used in this research is qualitative. Analysis of the data used is a qualitative analysis method. The results of this study indicate that the public's understanding of the services and products of Islamic banks in the interest of saving in Seri Tanjung Village, it can be concluded that people only know what Islamic banks are, but besides that, many people still do not understand Islamic banks. it in depth both in terms of services and products that exist in Islamic banks. So that people are less interested in saving in Islamic banks.